Value and Structure of Public Aid in Poland Against the European Union Background During the Years 2007-2012 - Kisiel, Roman; Kamińska, Małgorzata; Lizińska, Wiesława (Olsztyn Economic Journal, 2014)
Evaluation of changes in the value and structure of public aid in Poland and EU during the years 2007-2012 was the objective of the paper. The data from reports by the Office of Competition and Consumer Protection as well as data from the State Aid Scoreboard published by the European Commission based on the information provided by the Member States concerning that aid was used. In Poland, evident increasing trends of the horizontal aid value can be observed. In 2012, as compared to 2007, it increased by 0.5 billion euro to the level of 1.64 billion euro. Its share in the total value of support oscillates within 55-60% range. In the European Union that share is generally at the level of 70-74%. In Poland, the sectoral aid is limited gradually although its magnitude still differs from the Union standards. In 2012, the share of that aid was relatively small at ca. 14% while in the EU it was 12.9%. The regional aid is at the similar level both in Poland and in the EU oscillating around 20%. However, in 2012, the share of regional aid in Poland increased to the level of 26% and it was higher by 8 pp than the share of that aid in the EU. Significant differences are characteristic for the share of the aid in the GDP. During the period covered by the study the largest differences occurred in 2010 when the share of support in Poland was 1.7% of the GDP and in the EU 0.6% of the GDP. In 2012, a half of the public aid in Poland was allocated to large enterprises.